2019
DOI: 10.32910/ep.70.5.4
|View full text |Cite
|
Sign up to set email alerts
|

Export performance and competitiveness in wood products in the Czech Republic and Austria

Abstract: This article assesses the development of wood exports in the Czech Republic (Czechia) and Austria in recent years. Some approaches, such as revealed comparative advantage (RCA), relative trade balance index (RTB), and diversiÞ cation ratios are used to assess the export performance and competitiveness indicators in these countries. The RCA result reveals that both Czechia and Austria have been competitive in the global wood markets, just as the countries have witnessed positive in RTB within the period under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It has over 18,684 square kilometers of cultivable land, with one of Nigeria's most extensively irrigated lands. The city of Kano is a primary producer of groundnut in Nigeria, contributing significantly to the country being the largest producer in Africa, contributing over 30% of Africa's total groundnut production and the third (3rd) globally after China and India [33].…”
Section: Historical Development Of Kanomentioning
confidence: 99%
“…It has over 18,684 square kilometers of cultivable land, with one of Nigeria's most extensively irrigated lands. The city of Kano is a primary producer of groundnut in Nigeria, contributing significantly to the country being the largest producer in Africa, contributing over 30% of Africa's total groundnut production and the third (3rd) globally after China and India [33].…”
Section: Historical Development Of Kanomentioning
confidence: 99%
“…The factors of this transformation in the global competitiveness are correlated to the intense investments in the forest sector throughout the years, in addition to the fast growth of the Asian markets. Another factor that contributed to this change is the intensive forest activities in low productive cost regions such as south America (COELHO JUNIOR et al, 2018;HETEMAKI & HURMEKOSKI, 2016;SANTOS JÚNIOR et al, 2022;VERTER & GREGA, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The authors of several scientific studies have explored the possibilities of assessing the competitiveness of wood-based industries [23][24][25][26][27][28][29]. Works focusing on the analysis of competitiveness in Slovakia and Czechia have found that comparative advantages are below the EU average and their level is steadily decreasing.…”
Section: Introductionmentioning
confidence: 99%